Miki Takes a Bath Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Splish-splash! Miki’s taking a bath! Bathtime couldn’t be more fun with Miki showing how it’s done in this delightful pop-up …
Keywords: dept.lib